1997
DOI: 10.1111/j.1365-2796.1997.tb00022.x
|View full text |Cite
|
Sign up to set email alerts
|

No difference in blood thiamine diphosphate levels between Swedish Caucasian patients with congestive heart failure treated with furosemide and patients without heart failure

Abstract: . Yue Q‐Y, Beermann B, Lindstrom B, Nyquist 0 (Huddinge University Hospital, Huddinge, and the Medical Product Agency, Uppsala, Sweden). No difference in blood thiamine diphosphate levels between Swedish Caucasian patients with congestive heart failure treated with furosemide and patients without heart failure. Intern Med 1997; 242:49 1‐49 5. Objectives: To determine whether furosemide treatment in congestive heart failure (CHF) patients is associated with thiamine deficiency. Design: Patients without heart f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 16 publications
2
15
1
Order By: Relevance
“…This scenario suggests that a diet that meets the nutritional needs of persons not using diuretic therapy may not meet the needs of diuretic users. More importantly, studies have suggested previously that thiamin deficiency may not be common among diuretic users if the users are consuming a reasonable diet and thus can tolerate the negative impact of diuretics on thiamin metabolism (Hardig, Daae, Dellborg, Kontny, & Bohmer, 2000;Shimon, Almog, Vered et al, 1995;Yue, Beermann, Lindstrom, & Dyquist, 1997). The data presented here, however, demonstrate that dietary thiamin intake is not always adequate despite regular receipt of home-delivered meals among homebound older adults.…”
Section: Journal Of Nutrition For the Elderlycontrasting
confidence: 68%
“…This scenario suggests that a diet that meets the nutritional needs of persons not using diuretic therapy may not meet the needs of diuretic users. More importantly, studies have suggested previously that thiamin deficiency may not be common among diuretic users if the users are consuming a reasonable diet and thus can tolerate the negative impact of diuretics on thiamin metabolism (Hardig, Daae, Dellborg, Kontny, & Bohmer, 2000;Shimon, Almog, Vered et al, 1995;Yue, Beermann, Lindstrom, & Dyquist, 1997). The data presented here, however, demonstrate that dietary thiamin intake is not always adequate despite regular receipt of home-delivered meals among homebound older adults.…”
Section: Journal Of Nutrition For the Elderlycontrasting
confidence: 68%
“…Numerous factors have been reported to increase the risk of developing TD in CHF patients, including diureticinduced urine thiamin excretion (2)(3)(4)(5), severe heart failure (6), malnutrition (6,7), advanced age, and frequent hospitalizations (5,8 -12). The prevalence of TD in CHF patients has been reported to range from 3% to 91% (2,(5)(6)(7)12,13 ). Trials of thiamin supplementation, although clinically important, have been hampered by their small sample sizes, use of indirect measures of thiamin status, and exclusion of patients with less severe disease and those on diuretics other than loop diuretics (2,8,(11)(12)(13)(14)(15)(16)(17).…”
Section: Resultsmentioning
confidence: 98%
“…The prevalence of TD in CHF patients has been reported to range from 3% to 91% (2,(5)(6)(7)12,13 ). Trials of thiamin supplementation, although clinically important, have been hampered by their small sample sizes, use of indirect measures of thiamin status, and exclusion of patients with less severe disease and those on diuretics other than loop diuretics (2,8,(11)(12)(13)(14)(15)(16)(17). Therefore, the objective of this study was to determine the prevalence of TD in a large cross section of hospitalized CHF patients.…”
Section: Resultsmentioning
confidence: 98%
“…In patients with heart failure, the reported incidence of thiamine deficiency ranges from 13% to 93% [14][15][16][17][18][19]. There are numerous factors that have been found to be associated with thiamine deficiency in patients with heart failure including loop diuretic use [14,15], malnutrition [16,17], severe heart failure [16], advanced age and frequent hospitalizations [15,18,20,21].…”
Section: B Vitaminsmentioning
confidence: 99%